2018
DOI: 10.1038/s41419-018-1024-9
|View full text |Cite|
|
Sign up to set email alerts
|

Parkin-mediated mitophagy as a potential therapeutic target for intervertebral disc degeneration

Abstract: Intervertebral disc degeneration (IDD) is a complicated pathological condition blamed for low back pain. Mitochondrion is of vital importance for cellular homeostasis, and mitochondrial dysfunction is considered to be one of the major causes of cellular damage. Mitophagy is a cellular process to eliminate impaired mitochondria and showed protective effects in various diseases; however, its role in IDD is still not clear. Here, we explore the role of Parkin-mediated mitophagy in IDD. In this study, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 48 publications
1
77
0
Order By: Relevance
“…salidroside is also beneficial for IVDD in rats through the role of PRKN [17]. Their data indicate the role of PRKN in the eliminating of damaged mitochondria and NP cells survival.…”
Section: The Roles Of Mitophagy In Ivddmentioning
confidence: 86%
“…salidroside is also beneficial for IVDD in rats through the role of PRKN [17]. Their data indicate the role of PRKN in the eliminating of damaged mitochondria and NP cells survival.…”
Section: The Roles Of Mitophagy In Ivddmentioning
confidence: 86%
“…In MPTP-induced Parkinson's disease models, Sal can enhance the mitochondrial expression of PINK1 and Parkin and confer neuroprotective effects [31]. Another study showed that upregulation of Parkin by Sal promoted the survival of nucleus pulposus cells through activation of mitophagy in vitro [74]. Therefore, we evaluated the occurrence of mitophagy in Sal after SCIRI.…”
Section: Discussionmentioning
confidence: 99%
“…PINK1/ Parkin mitophagy pathway has been identified as a classical pathway involved in mitophagy 48 . Zhang et al reported that Parkin was involved in the pathogenesis of IVDD and may be potential therapeutic target for IVDD 49 . PINK1, Parkin and LC3 II are key proteins for mitophagy initiation, and p62 is indispensable for autophagic degradation 50 .…”
Section: Discussionmentioning
confidence: 99%